Effect of Heterogeneity and Heterozygosity on Agronomic Performance of the Semi-arid Grown Faba Bean (Vicia faba L.) (University of Khartoum Journal of Agricultural Sciences, 2022)
In faba bean, the genotypically heterogeneous structure of itspopulation has an important impact on yield performance and remains themajor constraint a plant breeder has to contend with to improve the cropyield. The aim of this study was to evaluate the effect of heterogeneity andheterozygosity on yield performance of the semi-arid grown faba bean. Fivefaba bean inbred lines (in S6 generation), F1 and F2 generations as well asmixtures formed by blending an equal amount of seeds from each of them toproduce line mixture, F-1 mixture and F2-mixtures were used to execute theexperiment. The seeds of the pure lines, lines mixture and F1-and F2-mixturewere grown in two consecutive seasons (2014/2015-2015/2016) at theExperimental Farm, Faculty of Agriculture, Shambat in a randomizedcomplete block design with three replicates. Data were collected on yield andyield components. Heterogeneity in lines mixture caused a positive andsignificant increase of +16% in number of pods per plant and 11% increase inboth 100-seed weight and yield compared to pure lines performance, whereasheterogeneity in "pure lines+ F1-hybrid and that in pure lines mixture+ F1-hybrid mixture gave significant positive yield of 28% and 24% , respectivelywhen compared to the performance of F2 and F2 mixture. Heterozygosity in F1 gave significant positive yield increase of 67% when compared to linesperformance, whereas heterozyosity in F1-mixture gave significant yieldincrease of 60% when compared to lines mixture. The same effect was shownby yield components. The results clearly indicate the great positive effect ofheterozyosity compared to that of heterogeneity, which indicate thepossibility of production of synthetic cultivars as alternative to the still notyet commercially produced hybrids in faba bean.